International Management as Management of Diversity: Reconceptualizing Distance as Diversity. (5th April 2021) - Lumineau, Fabrice; Hanisch, Marvin; Wurtz, Olivier
Abstract: Despite the importance of distance in international business and management research, the theoretical foundation for the concept and the underlying causal mechanisms are subject to shortcomings. We propose reinvigorating the study of distance through a diversity lens. We draw on research on diversity and develop a theoretical framework that distinguishes types of diversity (separation, variety, and disparity) at three levels (institutional, organizational, and individual). We show how this framework allows scholars to extend their analysis of distance, revisit important questions, and explore new issues. We discuss the theoretical and empirical implications of our diversity lens for the international business and management community.